If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + -1n = 2000 Solving 36 + -1n = 2000 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -1n = 2000 + -36 Combine like terms: 36 + -36 = 0 0 + -1n = 2000 + -36 -1n = 2000 + -36 Combine like terms: 2000 + -36 = 1964 -1n = 1964 Divide each side by '-1'. n = -1964 Simplifying n = -1964
| -(9y-14)=-15+29 | | x(2x-8)=-12 | | 19=-7(4k-9) | | 5(f+4)+9=-15 | | -7+4h=41 | | a+2=5+4a | | -9x-14=-15+29 | | -0.75n+7=25 | | 2+2x=4(2x+2)-7(x-1) | | 0.3(20X-30)=10 | | (3-2i)(7+6i)=0 | | 2(n-9)+8=-19 | | 20=-8a+9a | | 6y-8=9y+19 | | Ln(11x-3)=1.44567 | | 4x=x+17 | | 4/9x3/7x7/8 | | 8(2-z)+2(5z-4+a)= | | 2x+10=5x-25 | | 3x-120+5x=180 | | 8+4p= | | 16x-119=113-6x | | 7-(2(3-8x))=equation | | -8(2X-1.1)=28.8 | | 8(x)=2(x-7) | | 6(6y-5)-(9y+4)= | | 4xy/2x^2 | | -4(8z-7)=24 | | 2x*x=288 | | 1-10x=82 | | 5x+11+3x+10=2x+9 | | 9x*9x+6x+3=6 |